PENGARUH KUALITAS BARANG TRADING, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PT CITRA MANDIRI DISTRIBUSINDO - Kurniawan, Apri; Herman, Hendri (LPPM Universitas Putera Batam, 2019)
This study aims to determine whether trading product quality has a positive and significant effect on purchase decision, whether price has a positive and significant effect on purchase decision and whether service quality has a positive and significant effect on purchase decision. The independent variables in this study are trading product quality, price and service quality. While the dependent variable is the purchase decision. This research was conducted at Citra Mandiri Distribusindo Pte Ltd, using sample of 128 people. This research is quantitative and the data collection is done by collecting questionnaires by testing the quality of products, price and service quality partially with the help of SPSS (Statistics Product and Service Solution) version 21. The data analysis technique used in this research is descriptive analysis, data quality test, classical assumption test, influence test of multiple linear regression analysis, and hypothesis test in the form of t test and f test. The results of this study indicate that from the results of t test show the product quality has a positive and significant effect on purchase decision, price has a positive and significant effect on purchase decision and service quality have positive and significant influence to purchase decision. Based on the F test results, obtained the calculated F value of the product quality, price and service quality of 34.109 greater than F table of 2.680 and the significant values obtained 0.000 smaller than 0.05 which indicates that the product quality, price, and service quality simultaneously influence the purchase decision.